Lewis, Fischer 344, and Sprague-Dawley Rats Display Differences in Lipid Peroxidation, Motor Recovery, and Rubrospinal Tract Preservation after Spinal Cord Injury - Mestre, Humberto; Ramirez, Manuel; Garcia, Elisa; Martiñón, Susana; Cruz, Yolanda; Campos, Maria G.; Ibarra, Antonio (Frontiers in Neurology, 2015)
The rat is the most common animal model for the preclinical validation of neuroprotective therapies in spinal cord injury (SCI). Lipid peroxidation (LP) is a hallmark of the damage triggered after SCI. Free radicals react with fatty acids causing cellular and membrane disruption. LP accounts for a considerable amount of neuronal cell death after SCI. To better understand the implications of inbred and outbred rat strain selection on preclinical SCI research we evaluated LP after laminectomy sham surgery and a severe contusion of the T9 spinal cord in female Sprague-Dawley (SPD), Lewis (LEW) and Fischer 344 (F344) rats. Further analysis included locomotor recovery using the Basso, Beattie, and Bresnahan (BBB) scale and retrograde rubrospinal tract tracing. LEW had the highest levels of LP products 72 hours after sham surgery and SCI, significantly different from both F344 and SPD. SPD rats had the fastest functional recovery and highest BBB scores; these were not significantly different to F344. However, LEW rats achieved the lowest BBB scores throughout the two-month follow-up, yielding significant differences when compared to SPD and F344. To see if the improvement in locomotion was secondary to an increase in axon survival we evaluated rubrospinal neurons (RSN) via retrograde labeling of the rubrospinal tract and quantified cells at the red nuclei. The highest numbers of RSNs were observed in SPD rats then F344; the lowest counts were seen in LEW rats. The BBB scores significantly correlated with the amount of positively stained RSN in the red nuclei. It is critical to identify inter-strain variations as a potential confound in preclinical research. Multi-strain validation of neuroprotective therapies may increase chances of successful translation.